2008
DOI: 10.1093/humrep/den356
|View full text |Cite
|
Sign up to set email alerts
|

Engraftment potential of human placenta-derived mesenchymal stem cells after in utero transplantation in rats

Abstract: We conclude that hPMCs are mutipotent cells that can be engrafted long-term in immunocompetent rats after in utero transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 52 publications
2
36
0
Order By: Relevance
“…Besides the different methods of administration, the timing of delivery and number of cells delivered are also very important. Both higher numbers of MSCs and early phase delivery have been found to improve engraftment rates after the presentation of ischemia [72], and the protocol had been optimized [73].…”
Section: Engraftment Of Mscsmentioning
confidence: 99%
“…Besides the different methods of administration, the timing of delivery and number of cells delivered are also very important. Both higher numbers of MSCs and early phase delivery have been found to improve engraftment rates after the presentation of ischemia [72], and the protocol had been optimized [73].…”
Section: Engraftment Of Mscsmentioning
confidence: 99%
“…Thus, human MSCs from several sources have been shown to reconstitute different tissues after human-sheep [9][10][11], human-mouse [12,13], or human-rat [14] xenogeneic in utero transplantation. Furthermore, proof-of-principle studies have recently stressed the therapeutic potential of human fetal MSCs for the treatment of severe osteogenesis imperfecta both after xenogeneic transplantation into the corresponding mouse model [15], and after allogeneic transplantation in an immunocompetent, HLA-incompatible patient [16].…”
Section: Introductionmentioning
confidence: 99%
“…It was recently demonstrated that fetal membrane MSCs are capable of suppressing proliferation in a mix lymphocyte reaction, decreasing interferon (IFN)-ɣ and interleukin (IL)-17 production, stimulating IL-10 secretion, and increasing levels of adhesion markers CD54, CD29, and CD49d (29). In addition, placenta MSCs are able to engraft and survive long-term in various organs and tissues without evidence of inflammation or rejection after transplantation into neonatal animals and after in utero transplantation into pregnant rats (30,31 Before considering using placenta MSCs for clinical purposes, preclinical studies may be performed and the results must be carefully interpreted in order to assure safety for the patient and success in the therapy. Many preclinical studies on placenta-derived cells and amniotic membrane were reviewed (32), considering a wide range of diseases as neurological, pancreatic, muscle, vascular, cardiac, and pulmonary disorders along with liver fibrosis and applications for tissue engineering.…”
Section: Placenta-derived Stem/progenitor Cellsmentioning
confidence: 99%